2020
DOI: 10.1016/j.foreco.2019.117824
|View full text |Cite
|
Sign up to set email alerts
|

Potential climatic influence on maximum stand carrying capacity for 15 Mediterranean coniferous and broadleaf species

Abstract: Climate change projections for the Mediterranean basin predict a continuous increase in extreme drought and heat episodes, which will affect forest dynamics, structure and composition. Understanding how climate influences the maximum size-density relationship (MSDR) is therefore critical to designing adaptive silvicultural guidelines based on the potential stand carrying capacity of tree species. With this aim, data from the Third Spanish National Forest Inventory (3NFI) and WorldClim databases were used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 85 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…There is an advantageous growth at low density, as commonly observed in selective or future crop tree thinning systems for individual tree size growth acceleration [46]. Competition reduction enables an increase in stand density, mass production, and climate change mitigation through higher carbon storage [47][48][49]. Thinning reduced the tree layer C (Figure 1A) by removing the trees but promoting the tree biomass C growth by relieving the competition among trees for resources (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…There is an advantageous growth at low density, as commonly observed in selective or future crop tree thinning systems for individual tree size growth acceleration [46]. Competition reduction enables an increase in stand density, mass production, and climate change mitigation through higher carbon storage [47][48][49]. Thinning reduced the tree layer C (Figure 1A) by removing the trees but promoting the tree biomass C growth by relieving the competition among trees for resources (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and rainfall play a significant role in modifying both the slope and intercept of the maximum size–density relationship in a given species ( Kweon and Comeau, 2017 ; Andrews et al., 2018 ; de Prado et al., 2020 ). Latitudinal differences are closely related to climate conditions, which have implications for the growth and distribution of tree species.…”
Section: Discussionmentioning
confidence: 99%
“…Competition equivalence coefficient (CEC) compares species-specific growing space requirements of a species with their value in mixed stands, and it is calculated as the ratio of potential carrying capacity of both species in pure stands (by means of maximum stand density index [60]-SDI max ). Since recent studies have shown evidence that SDI max varies with climate [61,62], in this study we obtained climate-dependent CECs (Supplementary Table S2) to calculate species mixing proportions for each species in mixed stands using climate-dependent Maximum Size-Density Relationship (MSDR) models presented by Rodriguez-de-Prado et al [63].…”
Section: Mixing Proportion Influence On the H-d Relationship In Mixed Forest Standsmentioning
confidence: 99%